Danhong Injection for the Treatment of Hypertensive Nephropathy: A Systematic Review and Meta-Analysis - Li, YiZhuo; Yan, Shihai; Qian, Lichao; Wu, Lihua; Zheng, Yawei; Fang, Zhuyuan (Frontiers in Pharmacology, 2020)
Objective Danhong Injection (DHI) has been widely used to treat various diseases in China for many years. The objective of this systematic review was to evaluate the efficacy of DHI combined with antihypertensive drugs for treatment of hypertensive nephropathy. Methods Seven databases were searched from inception to September 21st, 2019. Randomized controlled trials comparing DHI combined with antihypertensive drugs versus antihypertensive drugs alone were extracted. The primary outcome was microalbuminuria (mALB). Secondary outcomes included systolic blood pressure (SBP), diastolic blood pressure (DBP), and serum creatinine (SCr). Results Fifteen studies were included in the meta-analysis, which indicated that DHI combined with antihypertensive drugs has advantages compared with antihypertensive drugs alone for reducing mALB [weighted mean difference (WMD) = −12.86, 95% confidence interval (CI) (−14.72, −11.0), P < 0.01], lowering SBP [WMD = −2.84, 95% CI (−4.56, −1.12), P = 0.001] and DBP [WMD = −2.38, 95% CI (−4.34, −0.43), P = 0.017], and decreasing SCr [WMD = −40.45, 95% CI (−55.69, −25.21), P < 0.01]. Conclusion The combination of DHI with antihypertensive drugs appears to be more effective than antihypertensive drugs alone for treatment of hypertensive nephropathy. A moderate duration (≤4 weeks) of DHI administration is reasonable, and longer treatment with DHI should be avoided, according to the results of subgroup analysis.